1989
DOI: 10.1017/s0043174500071885
|View full text |Cite
|
Sign up to set email alerts
|

Availability and Persistence of Imazaquin, Imazethapyr, and Clomazone in Soil

Abstract: The availability and persistence of imazaquin, imazethapyr, and clomazone were studied in a Cisne silt loam (1.3% organic matter) and a Drummer silty clay loam (5.8% organic matter). Availability of all three herbicides to bioassay species was greater in the Cisne soil than in the Drummer soil. Corn root growth was more sensitive to imazaquin and imazethapyr than corn shoot growth. Shoot and root growth of wheat was inhbited by similar clomazone concentrations. In field experiments conducted in 1984, 1985, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
91
2
4

Year Published

1991
1991
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(105 citation statements)
references
References 11 publications
8
91
2
4
Order By: Relevance
“…Imazaquin-phytotoxicity is lower in coarse-textured than in finetextured soils. The I50 for imazaquin was found to be 9 ppb in a silt loam and 73 ppb in a silt clay high organic matter loam soil (Loux et al, 1989). Herbicide effects on VAM root colonization are complex.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Imazaquin-phytotoxicity is lower in coarse-textured than in finetextured soils. The I50 for imazaquin was found to be 9 ppb in a silt loam and 73 ppb in a silt clay high organic matter loam soil (Loux et al, 1989). Herbicide effects on VAM root colonization are complex.…”
Section: Discussionmentioning
confidence: 99%
“…Although these herbicides are very selective, they can cause injury on susceptible crops (Barrett, 1989a, b;Loux et al, 1989;Renner et al, 1988). Crop phytotoxic symptoms include stunting, shortened internodes, deformed leaves, interveinal chlorosis, loss of apical dominance and premature senescence (Hess, 1989;Shaner, 1989b) and have been found to occur in double cropped soybeans and other crops (Barnes et al, 1989;Basham et al, 1987;Mills and Witt, 1989a, b;Renner et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in soil organic matter (OM), cation exchange capacity (CEC) and soil texture in two growing seasons may also have contributed to the observed differences between years for oilseed radish from imazethapyr residues. Many studies have reported the effects of soil OM, CEC and clay content on imazethapyr persistence (Loux et al, 1989;Goetz et al, 1990). Loux et al (1989) found that there was positive relationship between adsorption of imazethapyr and clay content.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported the effects of soil OM, CEC and clay content on imazethapyr persistence (Loux et al, 1989;Goetz et al, 1990). Loux et al (1989) found that there was positive relationship between adsorption of imazethapyr and clay content. According to Goetz et al (1990), lower degradation of imazethapyr was associated with greater adsorption in heavy textured soils with high OM and CEC content, resulting in increased imazethapyr persistence.…”
Section: Discussionmentioning
confidence: 99%